A case study of a novel longitudinal rural internship program - Jessica Beattie; Debra Hobijn; Lara Fuller (James Cook University, 2023)
Introduction: Rural medical training along all components of the medical training continuum has been shown to enhance rural workforce outcomes. However, due to the maldistribution of the Australian medical workforce, health services of increased rurality are limited in their ability to fulfil the supervision requirements for all levels of trainees, especially junior doctor training. Although longitudinal program design and pedagogy has flourished in medical school education through the Longitudinal Integrated Clerkship model, this has not yet been widely translated to prevocational training. This study describes how a longitudinal program design was conceptualised and implemented within a rural health service to create a novel internship program. Methods: A descriptive case study methodology was employed to describe and evaluate the longitudinal integrated internship program. Relevant program documents such as rosters and accreditation submissions were reviewed to aid in describing the program. Interviews with participants involved in the program were conducted during the middle (May) and end (November) points of the program's first year (2021) to investigate perspectives and experiences of the internship model. Results: Each week, interns were rostered for 1 day in the hospital's emergency department and 3 days in general surgery or general medicine, swapping disciplines after 6 months. In this way, interns completed core rotations longitudinally, meeting accreditation and supervision requirements. Additionally, 1 day per week was spent parallel consulting in general practice. Participants described program enablers as the organisational vision and staff buy-in, as well as the longitudinal attachments to disciplines. Barriers identified were the tenuous nature of the medical workforce and long-term sustainability of the program. Benefits of the program included value-adding and preparedness for practice, particularly in a rural context. Conclusion: Intern programs that meet the accreditation, supervision and learning requirements can be successfully delivered at rural health services through longitudinal models of medical education. As the intern year is a key component of the rural generalist training pathway, development of similar innovative models provides the opportunity for rural communities to grow their own future medical workforce.